2019
DOI: 10.1038/s41377-019-0200-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically encircling an exceptional point in anti-parity-time symmetric systems: asymmetric mode switching for symmetry-broken modes

Abstract: Dynamically encircling an exceptional point (EP) in parity-time (PT) symmetric waveguide systems exhibits interesting chiral dynamics that can be applied to asymmetric mode switching for symmetric and anti-symmetric modes. The counterpart symmetry-broken modes (i.e., each eigenmode is localized in one waveguide only), which are more useful for applications such as on-chip optical signal processing, exhibit only non-chiral dynamics and therefore cannot be used for asymmetric mode switching. Here, we solve this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(111 citation statements)
references
References 43 publications
4
107
0
Order By: Relevance
“…It is the unique property of CPA-LPs usually utilized for confirming CPA-LP in non-Hermitian systems. In the vicinity of the CPA-LP, the curves of the imaginary part are crossing, while the curves of the real part are anti-crossing [52]. The CPA-LPs are connected with the surface mode localized at the gain-loss boundary.…”
Section: Cpa-lps and Eps Splittingmentioning
confidence: 97%
See 2 more Smart Citations
“…It is the unique property of CPA-LPs usually utilized for confirming CPA-LP in non-Hermitian systems. In the vicinity of the CPA-LP, the curves of the imaginary part are crossing, while the curves of the real part are anti-crossing [52]. The CPA-LPs are connected with the surface mode localized at the gain-loss boundary.…”
Section: Cpa-lps and Eps Splittingmentioning
confidence: 97%
“…However, studies on non-Hermitian photonics have shown that loss and gain, satisfied with PT symmetry, provide a new degree of freedom for the system, which can effectively control photons and generate new optical effects, such as unidirectional reflectionless resonance, which can be used to prepare chip-level semiconductor lasers [48].Anti-PT-symmetric systems, in which the refractive index of material obeys n(x) = −n*(−x), have been proposed and attracted much attention [49][50][51]. Many interesting phenomena are found in anti-PT-symmetric systems, such as flat broadband light transport [50], and chiral mode conversion [52]. Actually, anti-PT symmetry belongs to a more fundamental symmetry called charge-conjugation symmetry [53,54], which consists of two sublattices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A new class of adiabatic protocols enables robust mode conversion in open systems that possess a special degeneracy called an exceptional point (EP)-where multiple modes of the system coalesce [1][2][3]. EP-based mode switches have intriguing physical properties, such as topological protection and non-reciprocity [4][5][6][7][8], which were demonstrated experimentally in optical waveguides and optomechanics [9][10][11][12][13][14] and theoretically proposed for several additional systems [15][16][17][18]. Realizing robust nonreciprocal mode switching in quantum systems has far reaching consequences in quantum information processing and quantum control, as well as in quantum technology.…”
mentioning
confidence: 99%
“…Typically, small perturbations in the operational details only slightly distort the loop or move the location of the EP, but do not lift the degeneracy. The possibility of creating a non-reciprocal switches between pure states has attracted considerable attention [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and, here, we generalize this concept for mixed states. Our protocol includes (i) finding an isolated EP in the eigenvalue spectrum of the NV center ( Fig.…”
mentioning
confidence: 99%